1988
DOI: 10.1007/bf02542540
|View full text |Cite
|
Sign up to set email alerts
|

Wetting properties of nonionics from branched fatty diamides

Abstract: Low pressure oxyethylation of RNHCOR CONHR or RCONHCH2CH2NHCOR does not occur below 100 C where R represents branched aliphatic groups and R’ is 0–4 methylene groups or ‐CH=CH‐. These diamides add ethylene oxide at 140–170 C to give dark adducts highly contaminated with aminoester. The corresponding dihydroxyethyl derivatives undergo low pressure oxyethylation, yielding products with good room temperature solubility, low aminoester content and good wetting properties for cotton skeins and a hydrophobic soil. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Compounds of structure {RN[(C 2 H 4 O) x H]C(O)} 2 Y, where Y is -CH 2 CH 2 -or -CH=CH-and R is 2-ethylhexyl, have been reported to be excellent hydrophobic soil wetting and rewetting agents (8). The acetylenic glycols of structure RR′C(OH)C≡CC(OH)R′R, where R′ is -CH 3 and R is a C 2 -C 4 alkyl group, are commercially available geminis that have been utilized for decades.…”
Section: Wettingmentioning
confidence: 99%
“…Compounds of structure {RN[(C 2 H 4 O) x H]C(O)} 2 Y, where Y is -CH 2 CH 2 -or -CH=CH-and R is 2-ethylhexyl, have been reported to be excellent hydrophobic soil wetting and rewetting agents (8). The acetylenic glycols of structure RR′C(OH)C≡CC(OH)R′R, where R′ is -CH 3 and R is a C 2 -C 4 alkyl group, are commercially available geminis that have been utilized for decades.…”
Section: Wettingmentioning
confidence: 99%
“…Linfield et al (9) have also reported that oxyethylated N,N'-dialkyl-N,N'-dihydroxyethyldiamides can be applied to soil wetting agents with excellent ability. However, there are only few reports on the interfacial properties of amphipathic compounds with both plural lipophilic and plural hydrophilic groups (10).…”
mentioning
confidence: 99%
“…[19] The dicarboxylate gemini [C 10 H 21 OCH 2 CH (OCH 2 COO À Na þ )CH 2 ] 2 Y, where Y is OCH 2 CH 2 O, have Draves skein wetting times at 0.1% concentration as 6 and 30 s, in comparision to 226 s for C 11 H 23 COO À Na þ . [20] The enhanced solubilization of water-insoluble matter is delineated by the geminis (RC 6 H 3 SO À 3 M þ )2O, which can remove stains from paints, inks, and other coloring materials from clothing and skin.…”
Section: Detergents Industriesmentioning
confidence: 99%